PENGARUH ASSET TURNOVER, CURRENT RATIO, DEBT TO EQUITY RATIO, DAN UKURAN PERUSAHAAN TERHADAP TERJADINYA UNDERPRICING SAHAM PADA PERUSAHAAN DI PASAR PENAWARAN SAHAM PERDANA YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2010-2014 - Maulidya, Putri Sesti; Lautania, Maya Febrianti (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2016)
The purpose of this research is to examine the influence of asset turnover, current ratio, debt to equity ratio, and company size on that occurs on initial public offering. Sampling techniques used in this research is purposive sampling with criterions companies listed in Indonesia Stock Exchange (IDX) that cinducted IPO during period 2010-2014, outside financial company sector, companies that underpriced, and companies which, have complete information. By those criterions, 71 companies were obtained as samples. The result of this research show that asset turnover, current ratio, debt to equity ratio, and company size silmutaneously influence to underpricing. Partially asset turnover has negative influence to underpiricing, current ratio has negative influence to underpricing, debt to equity ratio has positive influence to underpricing, and company size has negative influence to underpricing.Keywords Underpricing, Asset Turnover, Current Ratio, Debt To Equity Ratio, and Company Size